Novel FRF-based fast modal testing of multi-storey CLT building in operation using wirelessly synchronised data loggers. (31st March 2023) - Ao, Wai Kei; Pavic, Aleksandar; Kurent, Blaž; Perez, Fernando
Abstract: This paper presents a novel input–output frequency-response function (FRF) based field modal testing (MT) of an operational and fully occupied tallest cross-laminated timber (CLT) building in the U.K. A custom-built MT system and testing protocol were developed to facilitate exceptionally fast field testing work lasting only 10 h, including all instrumentation and field testing work. This yielded eight fundamental and higher-order modes of vibration with natural frequencies up to 12 Hz. The higher order modes are normally not possible to measure well enough using the standard output-only operational modal analysis (OMA). An FE model was developed prior to the testing to assure quality and facilitate the fast testing process. The FE model, based on the best engineering judgement, proved to be able to predict very well the key features of the test building. This includes close matching and correct clustering of the FE-calculated and MT-estimated natural frequencies, as well as a very reasonable prediction of the static stiffness at the top of the building. The in-situ measured horizontal static stiffness at the top of the CLT building is a considerable benefit of the field FRF measurements and is not possible in the standard OMA. It was shown that the preliminary best practice FE model was over-predicting the static stiffness in the two orthogonal directions by only up to 22% of the measured values. Curve-fitting of the good quality FRF data yielded damping ratio values for the higher order modes of vibration, typically above 3%. This is quite high for a full-scale multi-storey residential building.